Philosophical Thoughts of Muslim Thinker Ibn Rushd - Elsa Nurmalasari; Maspuroh; Asep Supriyadi; Maya Mardiana; Muhammad Gani Mulya Perdana (Penerbit Hellow Pustaka, 2025)
Ibn Rushd's philosophical thought is referred to by some Islamic thinkers as the last product of Islamic intellectual property with original, creative and innovative philosophical patterns because subsequently there were no significant developments but only theoretical explanations and deepening of studies. It is undeniable that the intellectual treasures left by Ibn Rushd are so large. Broadly speaking, it can be concluded that the philosophical school of Ibn Rushd is rational. It upholds reason and plays a major role in interpreting the realm of existence. It is as if Ibn Rushd's rational thought pattern represents the rational style of Western Islam (Morocco), which then clashes with the theological mindset and Eastern mysticism, represented by al-Ghozali. Experts say that the rationalism that became the style of Ibn Rushd’s thought was inseparable from the influence of Aristotle's philosophy, where Ibn Rushd was considered successful in teaching Aristotle's philosophy and was able to show the weaknesses of other Muslim theologians and philosophers. So according to Atef Iraqi, to fully understand Ibn Rusd's philosophy, one must also study Aristotle's philosophy. Ibn Rushd is considered by many scholars to be a true aristocrat. However, according to Mahmud Qasim, Ibn Rushd has distinctive originality of philosophical thought, unlike Renan's accusation. To see how far the originality of Ibn Rushd's philosophical thought is, this paper will attempt to review Ibn Rushd's philosophical thoughts which are mapped into the problems of cosmocentrism, ethnocentrism, and anthropocentrism.